TI_GERICHTE 52.2017.358 vom 9. Februar 2018 , Licenza edilizia in sanatoria per la posa di una casetta da giardino in un lido comunale - TI Tribunale d'appello (2018)
Licenza edilizia in sanatoria per la posa di una casetta da giardino in un lido comunale